The application of magnetite biochar composite derived from parthenium hysterophorus for the adsorption of methylene blue from aqueous solution - Teweldebrihan, Meseret Dawit; Gnaro, Mikiyas Abewaa; Dinka, Megersa Olumana (Frontiers in Environmental Science, 2024)
The removal of toxic and harmful dyes like methylene blue (MB) from textile wastewater is necessary to reduce environmental pollution. Therefore, this study is aimed at removing MB from an aqueous solution using magnetite-doped biochar of parthenium hysterophorus. Biochar was prepared through pyrolysis techniques at 500 ℃ for 2 h whereas the magnetite and composite material were developed using coprecipitation methods. Herein, NaNO3 and FeSO4. 7H2O were utilized as precursor materials and NaOH as a precipitating agent for preparation of magnetite. Furthermore, pH point of zero charge (pHpzc), Scanning Electron microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD) are characterization techniques used to evaluate the nature of the composite material. On the other hand, a full factorial design involving four factors at two levels (24) such as pH ( 3 and 9), contact time ( 10 and 40 min), initial dye concentration ( 100 and 150 mg/L) and adsorbent dosage of 0.01 and 0.04 g/100 mL was used to design and optimize the batch adsorption of MB from an aqueous solution. As a result, a maximum removal efficiency of 99.99% was attained at optimum operating conditions of pH 9, contact time 40 min, initial MB concentration 100 mg/L and adsorbent dosage of 0.04 g/100 mL. Langmuir, Freundlich and Temkin isotherm models were used to investigate the adsorption isotherm in which Freundlich isotherm with a maximum R2 of 0.98 was found to describe the adsorption process inferring multilayer and heterogeneous surface interaction. Additionally, the thermodynamics study depicts that the nature of the adsorption is spontaneous, endothermic and feasible. On the other hand, the chemosorption nature is revealed by the pseudo second kinetics model with a maximum R2 of 0.99. Finally, the remarkable reusability ranging from 99.98 to 97.6% for five consecutive cycles proved that the magnetic biochar derived from parthenium hysterophorus can be used as an effective adsorbent for the decolourization of MB saturated effluent at an industrial scale.